Mediation effects of post-series depression on the relationship between life satisfaction and positive mental health of Vietnamese: A cross-sectional study in COVID-19 pandemic context - Ngoc Nguyen, Be Thi; Huynh, Son Van; Nguyen, Trong Nguyen; Nguyen-Duong, Bao-Tran; Ngo-Thi, Thuy-Trinh; Tran-Chi, Vinh-Long (Frontiers in Psychology, 2022)
Vietnam, a middle-income country has been suffering four waves of Covid-19 pandemic and massive lockdown to suppress the spread of this infectious disease. As a consequence, COVID-19 has caused psychological ramifications and humankind life satisfaction. Because of the lockdown period, numerous people have plentiful time, hence, they found solace in excessive watching television and movies which could lead to post-series depression. The purpose of this study is to investigate the relationship between satisfaction of life (LS), post-series depression (PSD) and positive mental health (PMH), and inquire about the mediation effect of satisfaction of life and post-series depression. A total of 2,572 participants who were voluntarily recruited from various media platforms completed self-report questionnaires including Satisfaction with life scale, Post-series depression scale and Positive Mental Health Scale. This study was assessed by using the PLS-SEM approach. The findings of this research discovered (i) a significantly positive effect of LS on PMH; (ii) a significantly negative effect of PSD on PMH; (iii) a significantly negative effect of LS on PSD and (iv) a significantly indirect effect of LS on MH through PSD. The study provided additional evidence to the relationship between life satisfaction and positive mental health of individuals. Besides, the negative effects of post-series depression, which is a non-clinical term for feeling down that frequently appears after individuals finished their much-loved film and TV series, on individuals’ positive mental health is proved, especially in the COVID-19 pandemic context in which Vietnamese people must remain in their current location.